1979
DOI: 10.1093/nar/7.2.417
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of a highly repetitive component of rat DNA

Abstract: A highly repetitive component of rat DNA which could not yet be enriched by density gradient centrifugation was isolated with the help of the restriction nuclease Sau3AI. This nuclease converted the bulk of the DNA to small fragments and left a repetitive DNA component as large fragments which were subsequently purified by gel filtration and electrophoresis. This DNA component which was termed rat satellite DNA I is composed of tandemly repeated 370 bp blocks. According to sequence analysis the 370 bp repeats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1
6

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(45 citation statements)
references
References 37 publications
3
35
1
6
Order By: Relevance
“…This reflects that all EcoKI sites are not equally accessible and hence repeats of various lengths are generated. It is also reported that EcoRl sites present adjacent to methylated residues show slow accessibility to EcoRI [20]. Furthermore, a major portion of satellite DNA in high molecular weight range reflects higher order organization of the chromatin.…”
Section: Resultsmentioning
confidence: 96%
“…This reflects that all EcoKI sites are not equally accessible and hence repeats of various lengths are generated. It is also reported that EcoRl sites present adjacent to methylated residues show slow accessibility to EcoRI [20]. Furthermore, a major portion of satellite DNA in high molecular weight range reflects higher order organization of the chromatin.…”
Section: Resultsmentioning
confidence: 96%
“…Panel d shows the photograph and densitometric trace of a stained gel of total rat DNA digested with HaeIII. The sizes in kilobases of the indicated fragments were determined by comparison with the migration of appropriately sized marker DNAs and, for the blots shown in panels b and c, by rehybridizing these blots (after removing the first probe with alkali [65]) with a clone of rat satellite I DNA to detect the "ladder" of 370-bp monomer and its higher multiples that are generated by HaeIII digestion of satellite I (13,41). At least 70% of the stained 0.35-kb band in panel d is due to the HaeIII fragments derived from the ca.…”
Section: Methodsmentioning
confidence: 99%
“…Perhaps as striking is the fact that satellite DNA sequences account for only 1 to 2% of the total rat genome but 10 to 20% of the total DNA in mice or primates (38,41,52). Understanding the biological significance of these rather large-scale differences among the DNA composition of these animals should help determine the role or effect of repeated DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence homologies between C6 and 9L cells were recognised in the 167 and 203 bp fragments; these were identical to the consensus sequence for the 370 bp satellite DNA I obtained from Hind III-digested rat DNA. 8 Reaction of the end-labelled DNA fragments with ACNU or MCNU generated prominent bands, corresponding to positions of guanine in the original sequence through chemical cleavage (fig 2). The amount of radioactivity in bands corresponding to breakage at guanine positions was considerably higher than that observed for any other base.…”
Section: Resultsmentioning
confidence: 99%